Determination of paraneoplastic autoimmune responses by tumor cell biology and intratumoral IFN-alpha/IL-12 in breast cancer patients - Domschke, Christoph; Schütz, Florian; Ge, Yingzi; Rom, Joachim; Zorn, Markus; Sinn, Peter; Marmé, Frederik; Schott, Sarah; Heil, Jörg; Scharf, Alexander; Sohn, Christof; Schneeweiss, Andreas; et al. (Cancer immunology immunotherapy, 2011)
A wide variety of cancer types has been associated with paraneoplastic autoimmune disorders and with the induction of autoimmunity against several autoantigens, among them self-antigens that are also expressed by tumor cells. This raises the question of autoimmune disorders as a result of immune reactions to the tumor. To date, however, requirements for the generation of autoimmune reactions in cancer patients remain largely unclear. In this study, we characterized conditions in altogether 131 patients, which determine autoimmune responses in primary breast cancer patients. We used ex vivo IFN-γ EliSpot assays against autologous tumor or skin lysates to evaluate tumor- and auto-reactive T-cells (TCs) in the bone marrow (BM) as well as ELISA, ECLIA, and turbidimetric immunoassays for the detection of auto-reactive antibodies in the peripheral blood and compared results to intratumoral cytokine concentrations and pathobiological features of the primary tumor tissue. We here demonstrate a significant correlation between anti-tumor BMTC responses and cellular autoimmune reactivity in primary breast cancer patients (P = 0.002). Humoral autoimmune reactions, however, were negatively correlated with anti-tumor TC immunity (P = 0.039). We observed auto-reactive BMTCs especially in patients with well-differentiated, hormone receptor-positive carcinomas (P = 0.009). Furthermore, elevated concentrations of intratumoral IFN-α significantly correlated with the induction of cellular autoimmune reactivity (P = 0.0002), while humoral autoimmune reactions correlated with increased levels of intratumoral IL-12 (P = 0.04). Altogether, these data indicate a significant role of the tumor microenvironment and particularly that of IFN-α and IL-12 in the induction of systemic autoimmune responses and imply that the primary tumor tissue represents an integral site of autoimmune regulation in cancer patients.